EFFECT OF NEW COMPOSITION MICROBIOLOGICAL BIO PREPARATION ON MUNG BEAN PLANT PRODUCTIVITY - N. A. Khojamshukurov; F. A. Mustafaqulova; S. N. Mirzaabdullaeva (International Engineering Journal For Research & Development, 2020)
This article examines the effect of a new generation biopreparation (BtmsTr -biopreparati) based on metabolites of the fungus Trichodermaharzianum and the bacterium Bacillus thuringiensis on mung bean plant productivity. According to the results obtained, the melanin-synthesizing mutant strain of the bacterium Bacillus thuringiensisvar.thuringiensis and the ISK-synthesizing Trichodermaharzianumsp. BtmsTr-biopreparation prepared in a 1: 1 ratio from the culture fluids of strain 76 ,the productivity of mung bean was shown to be 77.4% higher than the control variant (Btnmsbiopreparation) or 61.4% higher than the template variant.Researches have shown that the production of this mungbean plant is caused by various aphids, beetles, caterpillars, moths, leaf-eating beetles and fungi that cause fusarium wilt, as well as microbiological objects that cause bacterial blight. Therefore, this biopreparation is recommended for use in increasing crop yields and combating various diseases and pests